Physical and biological properties of early winter Antarctic sea ice in the Ross Sea. Issue 83 (24th December 2020) - Tison, Jean-Louis; Maksym, Ted; Fraser, Alexander D.; Corkill, Matthew; Kimura, Noriaki; Nosaka, Yuichi; Nomura, Daiki; Vancoppenolle, Martin; Ackley, Steve; Stammerjohn, Sharon; Wauthy, Sarah; Van der Linden, Fanny; et al.
Abstract: This work presents the results of physical and biological investigations at 27 biogeochemical stations of early winter sea ice in the Ross Sea during the 2017 PIPERS cruise. Only two similar cruises occurred in the past, in 1995 and 1998. The year 2017 was a specific year, in that ice growth in the Central Ross Sea was considerably delayed, compared to previous years. These conditions resulted in lower ice thicknesses and Chl- a burdens, as compared to those observed during the previous cruises. It also resulted in a different structure of the sympagic algal community, unusually dominated by Phaeocystis rather than diatoms. Compared to autumn-winter sea ice in the Weddell Sea (AWECS cruise), the 2017 Ross Sea pack ice displayed similar thickness distribution, but much lower snow cover and therefore nearly no flooding conditions. It is shown that contrasted dynamics of autumnal-winter sea-ice growth between the Weddell Sea and the Ross Sea impacted the development of the sympagic community. Mean/median ice Chl- a concentrations were 3–5 times lower at PIPERS, and the community status there appeared to be more mature (decaying?), based on Phaeopigments/Chl- a ratios. These contrasts are discussed in the light of temporal and spatial differences between the two cruises.